GeoEcoMar activities dedicated to education and promotion of Earth Sciences (Geo-Eco-Marina, 2019)
Education was an objective of NRDI GeoEcoMar since its foundation, in order to attract young students to research through organizing various scientific meetings, summer schools, coordinating Master and PhD theses, etc. As European Centre of Excellence for Environmental and Geoecological Studies on River – Delta – Sea Systems in Europe – EuroGeoEcoCentre, during 2003-2006 the institute organized summer schools in the Danube Delta in order to train students from Romania and European countries in the sedimentology of terrestrial and marine systems. Since 2013, annual programs of education and internship for undergraduate students are run by the National Center for Monitoring and Warning on Marine Natural Hazards – Black Sea Security System – in Constanţa. Activities for schools and the general public started in 2010, with public conferences, temporary and travelling exhibitions, as well as various events. Such activities increased between 2016-2017, when a project dedicated to education and promotion of earth sciences was run by the institute. The educational program included educational activities for various types of target audience, activities of popularization and promotion of geological and paleontological sites in two Romanian geoparks, promotion of results accomplished by GeoEcoMar in earth sciences, ecology, marine biology, etc. The educational program developed was structured as education in schools, internship for students and geological literacy of the general public. For education in primary and secondary schools, ten lesson plans on earth sciences were elaborated, with associated hands-on activities. A 5 days field trip in Dobrogea was organized for undergraduate students, while various activities and events were proposed for the general public: public conferences, geological field trips, the Day of Open Doors at GeoEcoMar, Earth Science Week, the School Differently and workshops for children. Geological education is a necessity in Romania, especially as earth sciences do not have an adequate public presence and geological literacy of people is rather low. As geology is no longer part of the school curricula for almost 20 years, except some basic concepts included in the geography programs, education and promotion of earth sciences has to continue, which implies the existence of adequate financial and human resources.
Keywords: summer school; center of excellence; exhibitions; public conferences; events; educational package for schools